HIV Stigma and Social Capital in Women Living With HIV. (January 2017) - Cuca, Yvette P.; Asher, Alice; Okonsky, Jennifer; Kaihura, Alphoncina; Dawson‐Rose, Carol; Webel, Allison
Abstract : N/A: Women living with HIV (WLWH) continue to experience HIV‐related stigma. Social capital is one resource that could mitigate HIV stigma. Our cross‐sectional study examined associations between social capital and HIV‐related stigma in 135 WLWH in the San Francisco Bay Area. The mean age of study participants was 48 years; 60% were African American; 29% had less than a high school education; and 19% were employed. Age was significantly associated with perceived HIV stigma ( p = .001), but total social capital was not. Women with lower Value of Life social capital scores had significantly higher total stigma scores ( p = .010) and higher Negative Self‐image stigma scores ( p = .001). Women who felt less valued in their social worlds may have been more likely to perceive HIV stigma, which could have negative health consequences. This work begins to elucidate the possible relationships between social capital and perceived HIV stigma.